2001
DOI: 10.1016/s1534-5807(01)00087-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Abscisic Acid Signal Transduction and Biosynthesis by an Sm-like Protein in Arabidopsis

Abstract: The phytohormone abscisic acid (ABA) regulates plant growth and development as well as stress tolerance. The Arabidopsis sad1 (supersensitive to ABA and drought) mutation increases plant sensitivity to drought stress and ABA in seed germination, root growth, and the expression of some stress-responsive genes. sad1 plants are also defective in the positive feedback regulation of ABA biosynthesis genes by ABA and are impaired in drought stress induction of ABA biosynthesis. SAD1 encodes a polypeptide similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
271
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(291 citation statements)
references
References 34 publications
13
271
1
6
Order By: Relevance
“…The various posttranscriptional controls appear to be effected through the alteration of mRNA processing events including splicing, 3¢ end processing, nuclear export, transcript stability, and RNA degradation. A reporter system (the luciferase gene-coding region linked to an ABA-inducible promoter) was exploited to identify mutations resulting in increased ABA sensitivity-by identifying plants that showed abnormal bioluminescence in response to exogenous ABA (Xiong and others 2001). A further characterization of one of the mutants uncovered (sad1) indicated that it is indeed supersensitive to ABA (although it also displays reduced ABA biosynthesis), and one manifestation of this supersensitivity is an increased ability of ABA to inhibit seed germination and root growth and to enhance expression of some ABA-responsive genes (particularly ABA-dependent phosphatase type 2C genes, previously implicated as negative regulators of ABA signaling; Sheen 1998).…”
Section: Rna Transport/processing Proteinsmentioning
confidence: 99%
“…The various posttranscriptional controls appear to be effected through the alteration of mRNA processing events including splicing, 3¢ end processing, nuclear export, transcript stability, and RNA degradation. A reporter system (the luciferase gene-coding region linked to an ABA-inducible promoter) was exploited to identify mutations resulting in increased ABA sensitivity-by identifying plants that showed abnormal bioluminescence in response to exogenous ABA (Xiong and others 2001). A further characterization of one of the mutants uncovered (sad1) indicated that it is indeed supersensitive to ABA (although it also displays reduced ABA biosynthesis), and one manifestation of this supersensitivity is an increased ability of ABA to inhibit seed germination and root growth and to enhance expression of some ABA-responsive genes (particularly ABA-dependent phosphatase type 2C genes, previously implicated as negative regulators of ABA signaling; Sheen 1998).…”
Section: Rna Transport/processing Proteinsmentioning
confidence: 99%
“…It has been reported that stress causes enhancement of biosynthesis and accumulation of ABA and this enhancement can modulate physiological reaction in plant response to stress (Gómez-Cadenas et al, 1999). Also, it has been shown that the increase of ABA content under stress could be attributed to the synthesis of stress messenger ABA, which is possibly the result of feedback-stimulated expression of ABA biosynthetic gene (Xiong et al, 2001). ABA has been suggested to induce the gene expression of antioxidant enzymes and up regulate many stress responsive genes (Zhu, 2002;Gürsoy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As the first three proteins have been the subjects of a previous review [40], we describe them only briefly. abh1, sad1, and hyl1 mutants all show hypersensitivity to ABA during seed germination, but hyl1 and sad1 mutants appear to have more pleiotropic phenotypes [41][42][43]. The HYL1 protein contains two dsRBDs [41].…”
Section: Signalingmentioning
confidence: 99%
“…Both ABH1 and SAD1 appear to be the only Arabidopsis orthologs of subunits of basic RNA-processing machineries in yeast and metazoans [42,43]. Intriguingly, expression studies indicate that only a small set of mRNAs is affected by mutations in these genes, even by a null mutation in abh1 [42,43]. How mRNAs are specifically targeted by the machineries that involve ABH1 and SAD1 remains a mystery.…”
Section: Signalingmentioning
confidence: 99%